2014
DOI: 10.1080/1068316x.2014.951648
|View full text |Cite
|
Sign up to set email alerts
|

Participant gender, stalking myth acceptance, and gender role stereotyping in perceptions of intimate partner stalking: a structural equation modeling approach

Abstract: The present research used a mock juror experiment (N = 360) to assess two primary goals: (1) to examine the direct and indirect effects of participant gender, stalking myth acceptance, and gender role stereotyping on guilt ratings in a stalking trial; and (2) to examine the role of perceived victim fear and distress, and defendant intended danger on perceptions of a stalking trial. Using structural equation modeling, we found an indirect effect of participant gender, and both direct and indirect effects of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
(50 reference statements)
8
23
0
1
Order By: Relevance
“…We found that men blamed stalking victims and minimized stalking behaviors more than women did, and these findings have been previously noted (Dunlap, 2010;Dunlap et al, 2015;Lambert et al, 2013;McKeon et al, 2015;Sinclair, 2012). Furthermore, researchers have also found that women more readily perceive stalking behaviors and identify these behaviors as stalking compared to men (Chan & Sheridan, 2017;Phillips et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found that men blamed stalking victims and minimized stalking behaviors more than women did, and these findings have been previously noted (Dunlap, 2010;Dunlap et al, 2015;Lambert et al, 2013;McKeon et al, 2015;Sinclair, 2012). Furthermore, researchers have also found that women more readily perceive stalking behaviors and identify these behaviors as stalking compared to men (Chan & Sheridan, 2017;Phillips et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Other researchers have found that men typically blame victims of stalking and minimize stalking incidents more than women (Dunlap et al, 2015;McKeon et al, 2015;Sinclair, 2012). In general, men tend to minimize the seriousness of stalking behavior (e.g., fail to recognize stalking behavior as dangerous; Hall, 1998;Purcell et al, 2001).…”
Section: Gendered Perceptions and Experiences Related To Stalkingmentioning
confidence: 99%
“…(2015) report a three-factor structure: ‘stalking isn’t serious’, ‘stalking is romantic’, and ‘victims are to blame’. Dunlap et al. (2015) report a similar three-factor structure, emerging from their sample of US university students, which they describe as ‘minimising’, ‘flattery’, and ‘victim blaming’.…”
Section: Attitudinal Support For Stalkingmentioning
confidence: 93%
“…For example, McKeon et al (2015) report a three-factor structure: 'stalking isn't serious', 'stalking is romantic', and 'victims are to blame'. Dunlap et al (2015) report a similar three-factor structure, emerging from their sample of US university students, which they describe as 'minimising', 'flattery', and 'victim blaming'. Meanwhile, in their Italian university student sample, De Fazio and colleagues (2015) report two-factors emerging; one that taps into the notion that stalking is a nuisance or even flattering behaviour rather than a criminal act.…”
Section: Attitudinal Support For Stalkingmentioning
confidence: 94%
“…Similar to sexual victimization, the definition of stalking varies by jurisdiction and by study. Although it requires that the victim experience fear or a reasonable person would feel fear as a result of the offender’s behavior (Catalano, 2012; Sheridan, Blaauw, & Davies, 2003), legally defined stalking behaviors might mistakenly be perceived as “romantic” gestures from their partner (Belknap & Sharma, 2014), misinterpreted as harmless by victims (Cass, 2011), and accepted as less problematic by potential jurors—particularly males (Dunlap, Lynch, Jewell, Wasarhaley, & Golding, 2015). In reality, stalking is anything but harmless (Belknap & Sharma, 2014).…”
Section: Sexual Victimization and Stalking Experienced By College Studentsmentioning
confidence: 99%